Evaluation of the effect of Medicago sativa on Lipid Profile and Iron Indices in Healthy Volunteers: Evaluation of the effect of Medicago sativa on Lipid Profile and Iron Indices in Healthy Volunteers - Tavakkoli Ardakani, Maria; Agah, Fatemeh; Mojab, Faraz (Iranian Journal of Pharmaceutical Sciences, 2022)
Medicago sativa (alfalfa) has a long history of traditional use. Several studies indicate that the ingestion of M. sativa reduces cholesterol absorption and atherosclerotic plaque formation in animals and has been reported to be beneficial in the treatment of hemorrhage, as a tonic after blood loss and during anemia. Because hypercholesterolemia is an important risk factor for heart diseases and anemia is a common problem in developing countries, this double-blind, placebo-controlled, randomized clinical trial was designed to evaluate the effect of alfalfa extract on lipid profile and iron indices in healthy volunteers. 19 volunteers (all male) with an average age of 35 were elected for a randomized double-blind study. These volunteers were divided into two groups for drug (9 males) and placebo (10 persons). The capsules of 250 mg were taken three times a day for two months. Blood samples were collected at baseline, one month, and two months after taking the capsules. Ferritin, TIBC (Total Iron Binding Capacity), Iron, CBC (Complete Blood Count), cholesterol, triglyceride, LDL, and HDL were determined by laboratory testing standards. After two months in the treated group, serum iron showed more increase and TIBC factor decreased more in comparison with the control group and their LDL and triglyceride decreased and HDL increased but was not statistically significant. Alfalfa ethanolic extract, with 750 mg/day can help decrease LDL and triglyceride and increase HDL, and maybe increase serum iron as an adjunctive for hypercholesterolemia and anemia treatment.